2005
DOI: 10.1002/neu.20132
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic thermoprotection in a desert‐dwellingDrosophilaspecies

Abstract: Synaptic transmission is a critical mechanism for transferring information from the nervous system to the body. Environmental stress, such as extreme temperature, can disrupt synaptic transmission and result in death. Previous work on larval Drosophila has shown that prior heat-shock exposure protects synaptic transmission against failure during subsequent thermal stress. This induced thermoprotection has been ascribed to an up-regulation of the inducible heat-shock protein, Hsp70. However, the mechanisms medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…Prior evidence for thermoprotection of EJP parameters comes from a study of desert-adapted Drosophila, which maintain greater peak amplitude and area of the EJPs during heat shock than wild-type Drosophila (Newman et al 2005). However, in the current study, neither temperature at failure of EJPs, nor EJP amplitude or EJP half-width was altered in the overexpression groups.…”
Section: Synaptic Functioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Prior evidence for thermoprotection of EJP parameters comes from a study of desert-adapted Drosophila, which maintain greater peak amplitude and area of the EJPs during heat shock than wild-type Drosophila (Newman et al 2005). However, in the current study, neither temperature at failure of EJPs, nor EJP amplitude or EJP half-width was altered in the overexpression groups.…”
Section: Synaptic Functioncontrasting
confidence: 77%
“…We have previously shown that the cytoskeleton is important for neural thermotolerance in the locust Locusta migratoria (Klose et al 2004;Garlick and Robertson 2007), which may involve the action of sHsps as chaperones for actin filaments in the cytoskeleton during stress (Mounier and Arrigo 2002). We took advantage of the UAS/GAL4 overexpression system and examined several Drosophila Hsp26 overexpression genotypes during heat stress, and assessed crawling behavior and parameters previously linked with synapse function and stability, including morphology (Stewart et al 1996;DiAntonio et al 1999;Wan et al 2000), presynaptic integrity (Karunanithi et al 1999), and excitatory junction potential (EJP) responses in the muscle (Karunanithi et al 2002;Newman et al 2005). We expected that larvae overexpressing Hsp26 would exhibit conserved synaptic function at higher temperatures, that nerve firing and EJPs would fail at higher temperatures, and that EJP peak amplitude, area, and half-width would be greater than in controls during hyperthermia.…”
Section: Introductionmentioning
confidence: 99%
“…When the flies are pretreated just prior to measuring knockdown, the HSP profile during knockdown may be quite different due to the heat-shock response elicited by the pretreatment. We propose that the improved knockdown performance in LN females may be due to HSP70 induction, which appears to improve locomotor function in adults from some populations of D. melanogaster (Roberts et al, 2003;Newman et al, 2004;Klose and Robertson, 2004). It is unclear why the pretreatment had no significant effect on knockdown performance in LN males.…”
Section: Discussionmentioning
confidence: 93%
“…Relatively few studies have examined the impact of HSPs on locomotor function in insects, but one of the few is particularly germane to our current work (Newman et al, 2004). In the study, the effect of HSPs on locomotion was compared between a desert and a temperate species of Drosophila.…”
Section: Introductionmentioning
confidence: 99%
“…Drosophilids are model organisms in which thermotolerance has been studied extensively (Hoffmann et al, 2003) by a variety of methods, including assessment of mortality or survivorship following heat shock (Huey et al, 1991;Hoffmann et al, 1997;Berrigan and Hoffmann, 1998;Stratman and Markow, 1998;Berrigan, 2000;Sørensen et al, 2001;Folk et al, 2006;Rashkovetsky et al, 2006), knockdown time (McColl et al, 1996;Hoffmann et al, 1997;Berrigan and Hoffmann, 1998;Berrigan, 2000;Sørensen et al, 2001;Kellett et al, 2005), knockdown temperature (Gilchrist and Huey, 1999;Berrigan, 2000;Folk et al, 2006), and locomotor functioning during or following heat shock (Krebs et al, 2001;Zatsepina et al, 2001;Roberts et al, 2003;Newman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%